Efektivitas Teknik Rebozo Shake the Apple (RSTA) Terhadap Intensitas Nyeri Dan Lama Kala 1 Fase Aktif Pada Persalinan Ibu Multigravida: The Effectiveness of the Rebozo Shake the Apple (RASTA) Technique on Pain Intensity and Duration of the 1st Stage of the Active Phase in Multigravida Mother's Labor - Musliha, Iis (Dohara POAJ, 2023)
Introduction: Pain during labor if not resolved will result in prolonged labor which is the cause of maternal death by 4,3%. Various efforts have been made to reduce the rate of prolonged labor, one of which is the rebozo shake the apple tree technique. Based on the results of a survey conducted at the Manis Jaya Health Center in April 2022, out of 33 mothers giving birth, 11 mothers experienced prolonged labor. Methods: This study was a quasi-experimental design with a pre-post test control group design. The research sample for multigravida mothers was 30 respondents using a purposive sampling technique. Data were analyzed using the dependent t-test and independent t-test. Results: The results of the univariate analysis revealed that the average pain intensity of the intervention group before was 6,27 after 1,67 and the control group before was 5,93 after 3,33. The average duration of the first active phase of the intervention group was 152,67 minutes and the control group was 215,13 minutes. The results of bivariate analysis of the intensity of labor pain with a value of p = 0,001 <0,005 and the duration of the first stage of the active phase with a value of p = 0,000 <0,005. Discussion: There is the effectiveness of the Rebozo Shake the Apple Tree (RSTA) technique on the intensity of labor pain and the length of the first active phase. It is hoped that health workers can provide the Rebozo Shake the Apple Tree (RSTA) technique to reduce labor pain and speed up the delivery process.